Berberine-based carbon dots for selective and safe cancer theranostics. Issue 3 (3rd January 2018) - Zhang, Fan; Zhang, Ming; Zheng, Xiao; Tao, Songyuan; Zhang, Zhanqiang; Sun, Madi; Song, Yubin; Zhang, Jing; Shao, Dan; He, Kan; Li, Jing; Yang, Bai; et al.
Abstract : Fluorescent berberine-based carbon dots (Ber–CDs) were prepared through a facile synthesis strategy. Abstract : Fluorescent berberine-based carbon dots (Ber–CDs) were prepared through a facile synthesis strategy. Ber–CDs exhibited excellent optical properties for bioimaging and retained the biofunctions of berberine, and enabled selective and safe anti-tumor performance, demonstrating their promising application potential in cancer theranostics.